THE DIAGNOSTIC VALUE OF EEG AND BIOCHEMICAL MARKERS OF BRAIN INJURY IN HYPOXIC-ISCHEMIC ENCEPHALOPATHY - D. V. Blinov (Эпилепсия и пароксизмальные состояния, 2017)
Perinatal hypoxic-ischemic encephalopathy (HIE) is a one of common cause of damage to neonatal CNS. Electroencephalography (EEG) has diagnostic value for choice of therapeutic interventions and predicting of outcomes. Sarnat classification is used EEG findings. EEG-monitoring and amplitude-integrated EEG could be used in Intensive Care Unit to provide information about the prognosis for the infant. Comprehensive assessment based on EEG data and serum determination of biochemical markers of brain damage could be feasible for identifying risk of subsequent brain damage that might benefit for treatment and predict of outcomes after HIE. Further studies in this area are clearly needed.